Chemical Constituents of Carissa opaca Extracts and Their Evaluation as Antioxidants and Preservatives in Edible Oils - AKMAL KHAN*, MUHAMMAD; SHAHWAR, DURRE; AHMAD, NAEEM; KHAN†, ZAHEER-UD-DIN; AJAIB†, MUHAMMAD (Asian Journal of Chemistry, 2009)
Carissa opaca (Stapf ex Haines) leaves were extracted using Soxhletapparatus with petroleum ether (COE-PE), chloroform (COE-CH), ethylacetate (COE-EA), acetone (COE-AC), methanol (COE-ME), n-butanol(COE-BU) and water (COE-WA). Antioxidant potential of Carissaopaca extracts (COEs) was evaluated by four methods: ferric thiocyanate,thiobarbituric acid, scavenging of DPPH• and total antioxidant capacityalong with determination of total phenolics and antioxidant potential ofCOEs in peanut and sunflower oils. Results revealed that COEs hadsignificant antioxidant potential (inhibition of lipid peroxidation > 50 %)and DPPH· scavenging potential (scavenging > 80 %). Moreover, totalphenolic content was also higher in the extracts: COE-AC = 940 andCOE-BU = 600 mg of gallic acid equivalents (GAE). Application ofCOEs as natural antioxidants in peanut and sunflower oils significantlyreduced lipid peroxidation (inhibition > 60 %). A strong correlation oftotal phenols was observed with DPPH• and total antioxidant capacityassays (R2 = 0.9776 and R2 = 0.8104, respectively).